103 Expansion Duroplasty Improves Intraspinal Pressure, Spinal Cord Perfusion Pressure, and Vascular Pressure Reactivity Index in Patients With Traumatic Spinal Cord Injury. (August 2015) - Papadopoulos, Marios
Abstract : INTRODUCTION: We showed that, after traumatic spinal cord injury (TSCI), the injured cord is compressed by dura. Here, we show that laminectomy + duroplasty decompress the injured cord more effectively than laminectomy alone. METHODS: Open-label, prospective trial. Twenty-one patients with acute, severe TSCI (American Spinal Injury Association Impairment Scale Grades A, B or C) had realignment of the fracture and surgical fixation within 72 hours. Eleven patients had laminectomy (laminectomy group) and 10 had laminectomy and duroplasty (laminectomy + duroplasty group). Primary outcomes were magnetic resonance imaging (MRI) evidence of cord decompression (increase in intradural space, presence of cerebrospinal fluid around the injured cord) and spinal cord physiology (intraspinal pressure [ISP], spinal cord perfusion pressure [SCPP], spinal vascular pressure reactivity index [sPRx]). ISP was monitored from a pressure probe placed intradurally at the injury site, and arterial blood pressure was monitored from a catheter placed in the radial artery. SCPP = mean arterial pressure minus ISP. sPRx is the running correlation coefficient between ISP and arterial blood pressure. RESULTS: The laminectomy and laminectomy + duroplasty groups were well matched. Compared with the laminectomy group, the laminectomy + duroplasty group had greater increase in intradural space at the injury site (50% vs 20%, P < .05) and more effective decompression of the injured cord (78% vs 0% had MRI CSF signal round the injured cord, P < .01). In the laminectomy + duroplasty group, mean ISP was lower (12.7 vs 18.0 mm Hg, P < .01), mean SCPP higher (83.1 vs 66.8 mm Hg, P < .05) and mean sPRx lower (0.04 vs 0.14, P < .01), ie, improved vascular pressure reactivity, compared with the laminectomy group. Laminectomy + duroplasty caused CSF leak that settled with lumbar drain in 1 patient and pseudomeningocele that resolved completely in 5 patients. CONCLUSION: After TSCI, laminectomy + duroplasty improves spinal cord radiological and physiological parameters more effectively than laminectomy.